Tectonic and petrogenetic settings of the Eocene Challis-Kamloops volcanic belt of western Canada and the northwestern United States. Issue 18 (11th October 2022) - Dostal, Jaroslav; Jutras, Pierre
ABSTRACT: The Eocene Challis-Kamloops volcanic belt, which runs through the interior of British Columbia and northwest United States for >2, 000 km, developed within a short time interval from ~55 to ~45 Ma. Volcanic rocks of the belt are discontinuously distributed in a series of grabens, half-grabens and calderas. Although predominantly composed of high- to medium-K calc-alkaline rocks that are typical of continental arcs, they were extruded during a time of regional transtensional tectonics in the Cordilleran orogen, which also led to the contemporaneous emplacement of Precambrian metamorphic core complexes near the belt. Their relative contents in Y, Nb, La, Sm, Gd, Yb and Ta suggest that the magmas were formed in relation to slab-failure (slab break-off). Initial Sr and Nd isotopic ratios and neodymium depleted mantle model ages indicate that the northern and southern parts of the belt had isotopically distinct lithospheric mantle sources with, respectively, Palaeozoic to Mesozoic and Precambrian model ages. As all rocks of the belt share common tectonic and petrogenetic settings, greater contents in incompatible trace elements in rocks from the southern part of the belt suggest that the Precambrian sources were more metasomatically enriched in these elements than the Phanerozoic sources.